A survey of the training of traditional, complementary, and alternative medicine in universities in Thailand - Peltzer, Karl (J Multidiscip Healthc, 2019)
BACKGROUND: Traditional, complementary, and alternative medicine (TCAM) is popularly used by the Thai population. The aim of this study was to determine whether undergraduate medical curricula included TCAM and, if so, to ascertain what kind of education was provided. In addition, where undergraduate degrees in TCAM were offered, the type of TCAM curricula, research, training, and collaboration were examined. METHODS: In a cross-sectional survey, academic or curriculum deans and faculty at each of the medical schools (response rate 76.2% of 21) and each of the TCAM faculties and departments (response rate 77.8% of 18) in Thailand responded to a questionnaire on characteristics of their TCAM curriculum. RESULTS: Half of the medical schools (50%) confirmed the presence of TCAM education in their medical school, of which most were a required and some an elective course. In all surveyed 14 TCAM departments or faculties a bachelor’s degree and in five institutions a master’s degree in TCAM are offered. Undergraduate and postgraduate degrees include Thai Traditional Medicine, Applied Thai Traditional Medicine, Chinese Traditional Medicine, and Oriental Medicine. All the programs offered a research course and almost all indicated that their curriculum covers “scientific proofs about the efficacy and safety of treatments.” More than half (9) indicated that their curriculum covers “how TCAM professionals should interact with biomedical peers in their practice.” CONCLUSION: Regarding TCAM training modules of medical undergraduates, only 50% of medical schools had integrated TCAM training in their curriculum. It will be important to give all medical students exposure to TCAM practices in their curriculum. Regarding the implementation of TCAM bachelor’s degrees, the study confirmed the importance of the integration of research methodology, evidence-based health care, and interprofessional communication into the training of TCAM providers’ training and practice.